1985
DOI: 10.1111/j.1365-2559.1985.tb02446.x
|View full text |Cite
|
Sign up to set email alerts
|

An autopsy study of radial scar in the female breast

Abstract: In a study of breasts from 83 consecutive, unselected female autopsies, 23 women (28%) were found to have radial scars. The lesion was multicentric in 67% and bilateral in 43%. The frequency of radial scar was significantly increased among women with fibrocystic disease (43%) compared to women without this lesion (17%). No difference in the frequency of radial scar was registered between women with primary breast malignancy and women with either normal breasts or benign breast abnormalities. No radial scar dem… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
45
0
7

Year Published

1987
1987
2019
2019

Publication Types

Select...
6
1

Relationship

0
7

Authors

Journals

citations
Cited by 81 publications
(52 citation statements)
references
References 12 publications
0
45
0
7
Order By: Relevance
“…In contrast, a study by Anderson et al 27 concluded that the extent of tissue sampling was the likely determinant in RS detection rather than any association with malignancy. Subsequently, in a study of 83 consecutive, unselected female autopsies, Nielsen et al 26 found no difference in the frequency of RS between women with breast carcinoma and women with either normal breasts or benign breast disease. Similar to the results of the current study, they also found that the frequency of RS was significantly increased among women with fibrocystic disease (43%) compared with women without such changes (17%).…”
Section: Discussionmentioning
confidence: 97%
See 1 more Smart Citation
“…In contrast, a study by Anderson et al 27 concluded that the extent of tissue sampling was the likely determinant in RS detection rather than any association with malignancy. Subsequently, in a study of 83 consecutive, unselected female autopsies, Nielsen et al 26 found no difference in the frequency of RS between women with breast carcinoma and women with either normal breasts or benign breast disease. Similar to the results of the current study, they also found that the frequency of RS was significantly increased among women with fibrocystic disease (43%) compared with women without such changes (17%).…”
Section: Discussionmentioning
confidence: 97%
“…6 -8 However, subsequent autopsy and surgical studies examining the frequency of RS in women with breast carcinoma yielded conflicting results. [25][26][27] Wellings et al 25 found that the number of RS in extensively sampled breasts was greater in women with breast carcinoma than those without breast carcinoma. In contrast, a study by Anderson et al 27 concluded that the extent of tissue sampling was the likely determinant in RS detection rather than any association with malignancy.…”
Section: Discussionmentioning
confidence: 99%
“…This is not a distribution that is expected in screening. Virtually no relation was found between radial scars and carcinoma in studies of random autopsy and carcinoma-associated breast specimens, 14,40 although ra- dial scar was a very common histologic finding. Instances of radial scar with involvement by carcinoma/ lobular neoplasia also were described as a rare event in the high-volume practice of the Armed Forces Institute of Pathology.…”
Section: Discussionmentioning
confidence: 98%
“…Several studies have evaluated the frequency of radial scars in women with breast cancer, but with conflicting results. [16][17][18][19] The few clinical follow-up studies that have been performed have not demonstrated an increased risk of cancer among women with radial scars, but these studies were small and lacked suitable controls. 20,21 To examine the association between the presence of radial scars and the subsequent risk of breast cancer in women with various categories of benign breast disease, we conducted a case-control study within the Nurses' Health Study, which is a long-term, prospective study of risk factors for breast carcinoma in women in the United States.…”
Section: Discussionmentioning
confidence: 99%